2015
DOI: 10.1073/pnas.1416117112
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic flux controls d -serine synthesis through glyceraldehyde-3-phosphate dehydrogenase in astrocytes

Abstract: D-Serine is an essential coagonist with glutamate for stimulation of N-methyl-D-aspartate (NMDA) glutamate receptors. Although astrocytic metabolic processes are known to regulate synaptic glutamate levels, mechanisms that control D-serine levels are not well defined. Here we show that D-serine production in astrocytes is modulated by the interaction between the D-serine synthetic enzyme serine racemase (SRR) and a glycolytic enzyme, glyceraldehyde 3-phosphate dehydrogenase (GAPDH). In primary cultured astrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…Accordingly, (Suzuki et al . ) using SR‐KO as negative controls recently report that astrocytes abundantly express SR in the human subiculum thus supporting the notion that SR and d ‐serine are present in astrocytes in vivo (Ma et al ., , Martineau et al ., ). Thus, the cellular distribution of SR remains an open issue particularly as a recent transcriptome analysis of isolated purified brain cell groups shows that the enzyme is more expressed in glia cell lineage and notably astrocytes than in neurons in the mature cortex of mice (Zhang et al .…”
Section: Structure and Subunit Diversity Of Nmdars In The Cnssupporting
confidence: 63%
“…Accordingly, (Suzuki et al . ) using SR‐KO as negative controls recently report that astrocytes abundantly express SR in the human subiculum thus supporting the notion that SR and d ‐serine are present in astrocytes in vivo (Ma et al ., , Martineau et al ., ). Thus, the cellular distribution of SR remains an open issue particularly as a recent transcriptome analysis of isolated purified brain cell groups shows that the enzyme is more expressed in glia cell lineage and notably astrocytes than in neurons in the mature cortex of mice (Zhang et al .…”
Section: Structure and Subunit Diversity Of Nmdars In The Cnssupporting
confidence: 63%
“…). Previously, GAPDH has been reported to control d ‐serine production in the hippocampus by interacting with serine racemase, which converts l ‐serine into d ‐serine, thereby influencing glutamatergic neurotransmission . Serine metabolism is critical for cancer cells, and the diversion of glycolytic flux to serine metabolism contributes to tumor progression .…”
Section: Discussionmentioning
confidence: 99%
“…SR was virtually completely neuronal, with only trace astrocytic expression in the cortex and hippocampus [31]. Recently, low astrocytic SR staining was detectable in mouse hippocampus, only after the use of an amplification method [32], confirming the scarcity of astrocytic SR in vivo . Furthermore, Balu et al used an SR antibody validated with brain tissue from SR−/− mice and found that SR was expressed in pyramidal and inhibitory neurons but not in S100β–containing astrocytes in human primary motor cortex [33].…”
Section: D-serine and Sr Are Mainly Neuronalmentioning
confidence: 99%